Moderate hypothermia at 29.5 °C in a patient without neurocognitive alterations: a case report - Arianna Merra; Luca Tagliabue; Adam-Scott Feiner (Journal of Medical Case Reports)
Abstract Background Hypothermia is typically associated with neurocognitive impairment, particularly as core temperature drops. However, cases without such symptoms are rarely reported. This case highlights an unusual presentation of moderate hypothermia without cognitive dysfunction, raising questions about individual variability in clinical manifestations. Case presentation A Swiss Caucasian female patient in her early 50s with a known history of psychiatric disorders presented to the emergency department with a core body temperature of 29.5 °C, consistent with moderate hypothermia. Remarkably, she was alert, oriented, and exhibited no signs of neurocognitive impairment, such as confusion, memory loss, or altered mental status. Her vital signs were stable, and laboratory and imaging studies excluded common causes such as infection, intoxication, or endocrine dysfunction. She was treated with passive external rewarming and careful monitoring. Her clinical condition improved steadily, and she was discharged without complications or neurological deficits. Conclusion This case demonstrates that moderate hypothermia may, in rare cases, present without neurocognitive alterations. It challenges the conventional association between hypothermia severity and mental status changes and suggests the need for further investigation into the physiological mechanisms behind this variability.